Variation of pore structure of organosilicone‐modified skin collagen matrix. Issue 19 (16th January 2017) - Li, Yupeng; Wang, Baochuan; Li, Zhengjun; Li, Lixin
ABSTRACT: The pore structure of skin collagen matrix modified by organosilicone alone, combination of organosilicone and chromium respectively, was investigated mainly through nitrogen adsorption, scanning electron microscopy and fractal analysis. The results indicated that increasing the dosage of organosilicone endowed more numbers of uniform smaller pores, increased porosity in modified collagen matrix and improved thermal stability verified by differential scanning calorimeter analysis. A similar trend was observed after incorporating less amount of chromium to organosilicone modification in the process. It can be presumed that a rigid and stable three‐dimensional silica network structure formed in the interior of the collagen fiber plays a role in fixing the collagen molecular chain, conferring improved hydrothermal stability to the skin matrix. The findings are of great significance to explore chrome‐less and further chrome‐free silicone tanning technology, and are helpful to promote sustainable development of the leather industry. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44831. Abstract :